PREVENTION OF KHALITYA (HAIR FALL) THROUGH AYURVEDA: A REVIEW - Sharma Renu; Anita Sharma (International Journal of Applied Ayurved Research, 2020)
Khalitya (Hair fall) affects men and women of all ages and often significantly affects social and psychological wellbeing. In current era are prone to sedentary life style this result in disturb routine, irregular dietary habit, lack of physical activity, stress etc. these are most common cause of khalitya (hair fall). Hair growth is impacted by today’s life style choice, faulty dietary habits, environmental pollution etc . Life vicissitudes, including illness, emotional trauma, protein deprivation (during strict dieting) and hormonal changes like those in pregnancy, puberty and menopause may cause hair fall .Several health condition including thyroid disease, iron deficiency anaemia can cause hair loss. To prevent hair fall we have adopt holistic approach to follow the life style as explained in Ayurveda. We cannot focus on single dimension like only dincharya or ritucharya. We have to focus multi-dimensionally on dincharya, aahara, vihara, nindra, avoidance of vegdharana, yoga and pranayama etc. to handle the problem of hair fall and achieving the good physical, mental, social and spiritual health.